Nurses' and midwives' experiences and views about responding to out of work emergencies: A constructivist grounded theory study - Crouchman, Carolyn; Griffiths, Lauren; Harris, Ruth; Henderson, Keiran (Journal of advanced nursing, 2022)
Aim To explore nurses' and midwives' experiences, views, perceptions and impact on their responses to out of work emergencies where first aid may be required. Design A constructivist grounded theory study was conducted between 2012 and 2019. Methodology In‐depth, semi‐structured interviews were undertaken with 16 nurses and midwives. Participants were recruited via a participant referral process with registered nurses and midwives being accessed from three NHS organizations. Data were analysed and coded using constant comparative analysis with the support of Nvivo 10 software leading to the construction of a substantive grounded theory. Results A core enduring in vivo theme, ‘The Right Thing to Do’, emerged as a central conceptual reality constructed via three key in vivo themes; ‘Something I've Heard’, ‘Am I Covered?’ and ‘Just Who I Am’, each with several sub‐themes. A pervading anxiety about responding at off‐duty situations requiring first aid was persistently evident across these themes. Conclusion The study showed a strong sense of moral agency among nurses and midwives, despite a powerful underlying feeling of anxiety surrounding broader issues of urban myth, protection and personal and professional identity. The substantive theory emerged as ‘doing "The Right Thing" in a climate of anxiety’. Impact The study illuminates an area that has previously been the subject of anecdotal debate. The substantive theory, ‘doing "The Right Thing" in a climate of anxiety’ illustrates the issues and tensions that exist surrounding the off‐duty response. Implications and recommendations for practice and education focus on the fostering of knowledge and understanding of professional identity, position in law and scope of practice, together with potential future research directions. This work provides the first in‐depth qualitative study contributing a significant new perspective both nationally and globally.